Asymmetrically CPW-Fed Hourglass Shaped UWB Monopole Antenna with Defected Ground Plane - Singhal S.; Singh A.K. (My University, 2025)
A compact hourglass shaped monopole antenna structure for UWB applications is presented in this paper. It consists of an hourglass shaped radiating patch and rectangular CPW ground plane with rectangular notches. Asymmetrical patch feeding and defected ground structure are utilized to achieve an usable bandwidth ranging from 3.75 to 19 GHz (134 %) below the VSWR < 2 line. The presented antenna has nearly omnidirectional and dipole shaped radiation patterns at lower operating frequencies. The radiation patterns got directional at higher frequencies. It has an acceptable value of group delay and gain. The antenna design is simulated using FEM based HFSS software. Another simulation software CST MWS, based on FIT technique, is used to carry out the time domain analysis of the designed antenna structure. The simulation and experimental results are found to be in good agreement with each other. © 2016, Springer Science+Business Media New York.